2004
DOI: 10.1111/j.0026-7902.2004.00227.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Successful and Unsuccessful EFL Students in Chinese Universities

Abstract: Unlike success in first language acquisition, success in learning a second or foreign language is considerably more variable. Recently, second language acquisition researchers have called for more integrative research on individual difference factors. With this goal in mind, this study followed a larger, quantitative study of the links between self-directedness for language learning and English language learning attainment among university students on the Chinese mainland and in Hong Kong. Drawing on the findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
120
2
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(130 citation statements)
references
References 37 publications
6
120
2
2
Order By: Relevance
“…In the extent of anxiety level, however, less effective learners were, in general, more worried about listening comprehension than effective learners. In addition, it was found that the anxiety level was reversely related to the confidence level because effective learners were more confident and less worried in their listening comprehension than less effective learners (Gan et al, 2004). It is noteworthy that when L2 learners are worried too much and have low confidence in performing listening tasks, their cognitive system and affective system do not function normally and block their comprehension tasks.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the extent of anxiety level, however, less effective learners were, in general, more worried about listening comprehension than effective learners. In addition, it was found that the anxiety level was reversely related to the confidence level because effective learners were more confident and less worried in their listening comprehension than less effective learners (Gan et al, 2004). It is noteworthy that when L2 learners are worried too much and have low confidence in performing listening tasks, their cognitive system and affective system do not function normally and block their comprehension tasks.…”
Section: Discussionmentioning
confidence: 97%
“…In quantitative studies, the studies to date have shown generally statistically significant but low correlations between strategy use and L2 proficiency (Griffiths, 2003;Nisbet et al, 2005;Phakiti, 2003). In qualitative studies, effective learners have not always used different learning strategies than less effective learners, depending on different learners in different learning contexts (Gan et al, 2004;O'Malley et al, 1989;Vandergrift, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we should not ignore cultural differences, and should indeed design our distance language courses and tailor our learner support to take account of them, it is equally important that we work to achieve this in the context of a wider heterogeneity and avoid, as Sanchez and Gunawardena (1998) caution, making generalizations about individuals based on knowledge about specific culturally defined groups. There is some evidence from other studies (Gan et al, 2004;Gieve & Clark, 2005) that Chinese students, particularly those learning English in distance mode, are becoming increasingly aware of the benefits of autonomous study, and that 'apparently stable, culturally determined approaches to learning are far more flexible to contextual variation than we might expect' (Gieve & Clark, 2005, p. 262). This was borne out by this study in that 91.3% of SRTVU students considered that changes in learning approach were possible.…”
Section: Resultsmentioning
confidence: 99%
“…It should be seen as a useful starting point for further research in this area, particularly in relation to the interpretation and practice of learner autonomy in distance as opposed to face-to-face language learning, across different cultures, and the issues this raises for curriculum design. Given the increasingly held view that language learning is 'culture-bound'-in other words, that learning a language is inextricably linked to learning about the target language culture (Palfreyman & Smith, 2003;Gan et al, 2004)-other research routes might link more explicitly the 'distance' factor in language learning to the development of intercultural awareness, and seek to identify in what ways this might be significant in comparison with classroom-based learning situations. The relationship between motivations and aspirations among learners from different cultures studying a language in distance mode and the development of intercultural competence as a learning goal might also be a fruitful area to research.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%